Development of wireless tri-axial fluxgate magnetometer for geomagnetic monitoring / Ahmad Faizal Zainal Abidin - Zainal Abidin, Ahmad Faizal (2018)
Conventional observatory grade magnetometer for geomagnetic monitoring purpose offers high end sensing performance in terms of sensitivity, reliability and stability. The robustness comes with bulky part-by-part system contributing to large physical dimensions and high cost. Hence, these become the limiting factors of magnetometer array expansion. Serial cable contributes to extra load (up to 4.5 kg for 70 m long) and effort for installation.